2022
DOI: 10.1097/mbp.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

White-coat effect on orthostatic hypotension: a nationwide survey of Japanese general practitioners

Abstract: Objective The relationship between the white-coat effect (WCE), defined as white-coat hypertension under treatment, and the frequency of orthostatic hypotension (OH) is not known. We conducted an orthostatic test in patients with WCE to determine the frequency of OH. Methods This was a cross-sectional study of 5631 patients with hypertension visiting general practitioners nationwide, in which 4305 patients with hypertension recorded their home blood pressure (BP) and consented to the orthostatic test. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…WCE is often present among older adults and represents a state of discordant BP in clinic and at home [33,34]. Adults with WCE have low or normal BPs measured via ambulatory BPs at home versus elevated or high BPs in clinic, and some speculate that these adults may be at a greater risk of hypotensive events or syncope from hypertension treatment [24,35,36]. The role of sympathetic hyperactivation in the clinic setting has been well-described [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…WCE is often present among older adults and represents a state of discordant BP in clinic and at home [33,34]. Adults with WCE have low or normal BPs measured via ambulatory BPs at home versus elevated or high BPs in clinic, and some speculate that these adults may be at a greater risk of hypotensive events or syncope from hypertension treatment [24,35,36]. The role of sympathetic hyperactivation in the clinic setting has been well-described [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…48 One study involving 4305 patients with hypertension demonstrated that early OH (OH within 1 minute of standing) was present in ≈7% of those with white-coat hypertension. 49 Another study examining 897 adults (a subpopulation of SPRINT) undergoing BP treatment showed that OH was positively associated with white-coat effects. 50 Another common pattern is nocturnal nondipping (ie, the absence of a normal drop in BP while asleep) or nocturnal hypertension (high BP while sleeping), [50][51][52][53] which may be more pronounced in older adults because of aging-related changes in circadian BP regulation 54 and could reflect an incipient neurodegenerative disorder (see the discussion of neurogenic OH).…”
Section: Oh Characterizationmentioning
confidence: 99%
“…48 One study involving 4305 patients with hypertension demonstrated that early OH (OH within 1 minute of standing) was present in ≈7% of those with white-coat hypertension. 49 Another study examining 897 adults (a subpopulation of SPRINT) undergoing BP treatment showed that OH was positively associated with white-coat effects. 50…”
Section: Pathophysiologymentioning
confidence: 99%
“…12 OH also associates with distinct ambulatory BP phenotypes. 14,16 In a subgroup analysis of 849 adults from SPRINT, OH was found to be associated with white coat hypertension (a state where BP measured in the clinic are higher than BP measured at home) and nocturnal elevations in BP. 13…”
Section: Oh As a Clinical Assessment Predicting Hypotensive Events An...mentioning
confidence: 99%
“…11 Along these lines, OH has been shown to be useful in predicting hypotensive events 12 as well as patterns of BPV outside of the clinic among adults with hypertension. [13][14][15][16]…”
Section: Hypertension and Blood Pressure Dysregulationmentioning
confidence: 99%